Indicator based ecotourism planning - Mirjana Bartula; Viktor Radun (UTMS Journal of Economics, 2023)
There is a growing interest for sustainable tourism and ecotourism on a global level. The concept of ecotourism stresses the human responsibility to the natural environment in a way that ensures the sustainable and responsible relationship of tourism and travel industry to environment. Ecotourism is particularly important as it succeeds in having minimum impact on natural resources while providing maximum economic benefit for the local communities. However, ecotourism has to be carefully planned taking into account environmental, economic, socio-cultural, experiential and managerial indicators. This paper considers development of indicators framework as a tool for sustainable management od ecotourism destination.
Keywords: C1; C32; C35; 330; ecotourism; indicators; management